If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6z + -14z = 48 Combine like terms: 6z + -14z = -8z -8z = 48 Solving -8z = 48 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Divide each side by '-8'. z = -6 Simplifying z = -6
| -1/5x=-8 | | -9x-1=-4x-2 | | 6x^3+72x^2-78x=0 | | 7m+4m=77 | | 5=-8.7+6x | | f(x)=5cos(x) | | 3/4=15/x2 | | -4x^2-52x+120=0 | | 3(x-5)2(x-1)=8 | | 4(5x+4)=236 | | 8t+48t+t^2= | | 2x^3-32x^2+78x=0 | | 2w-4=4 | | 7-3*2+6+3=35 | | 1.86=6.2a | | 25x^3-15x^4=5x^3 | | -30+5(x-2)=4x+7 | | 9-7x=42+(-4x) | | 3x^2-58x-40=0 | | 3ab-2b=3a-b | | -3x^2-3x+90=0 | | 1.2y-0.3x=0.12 | | -7x-5y=11 | | X/11=-22 | | f(x)=2x^2-16x+27 | | 3Y-9-3Y=-9 | | 1.2x-0.3y=0.12 | | 12-7x=9x-5x-87 | | 4x^3+72x^2+68x=0 | | 5/6-x/6=6/5 | | 2^3*x=1/64 | | 3x-5x+4-x+7=88 |